Botánica Forense en Chile: El caso de Aristotelia chilensis (Molina) Stuntz y su potencial utilidad como especie bioindicadora forense - Romero-Mieres, Mario; Vivallo, Gabriel; Donoso, Gustavo; Esse, Carlos; Díaz, Ramiro; Francois, Angélica; Solano, Jaime; Ortloff, Alexander; Albornoz, Sandra; Betancourt, Oriana; Cofré, Ximena; Valdivia, Margarita; et al. (Gayana Botánica, 2016)
Aristotelia chilensis is mentioned for the first time for plants grown on pig carcasses decomposing. Its potential as a bioindicator species for the development of forensic botany in Chile and its importance in the reconstruction of criminal events are discussed.